Archaeology and biblical interpretation - Bartlett, John R. (John Raymond) (Routledge, 1997)
Uses the most recent research in key areas - early settlements of Israel, early Israelite religion, Qumran, Jerusalem, early Christian churches - showing that ancient writings and modern archaeology can illuminate each other.